Microporous La–Metal–Organic Framework (MOF) with Large Surface Area. Issue 7 (17th December 2014) - Pal, Souvik; Bhunia, Asamanjoy; Jana, Partha P.; Dey, Subarna; Möllmer, Jens; Janiak, Christoph; Nayek, Hari Pada
Abstract A microporous La–metal‐organic framework (MOF) has been synthesized by the reaction of La(NO3)3⋅6 H2O with a ligand 4, 4′, 4′′‐s‐triazine‐1, 3, 5‐triyltri‐p‐aminobenzoate (TATAB) featuring three carboxylate groups. Crystal structure analysis confirms the formation of 3D MOF with hexagonal micropores, a Brunauer–Emmett—Teller (BET) surface area of 1074 m2 g−1 and high thermal and chemical stability. The CO2 adsorption capacities are 76.8 cm3 g−1 at 273 K and 34.6 cm3 g−1 at 293 K, a highest measured CO2 uptake for a Ln–MOFs.